2015
DOI: 10.1097/nen.0000000000000235
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study: Comparison of Frontal Cortex Needle Core Versus Open Biopsy for Detection of Characteristic Proteinopathies of Neurodegenerative Diseases

Abstract: The clinical diagnosis and classification of neurodegenerative diseases based on clinical examination or available biomarkers are currently insufficiently accurate. Although histological examination is considered the gold standard for diagnosis, brain biopsies have been avoided because of the high risk-benefit ratio. However, brain biopsies have previously been performed with a craniotomy and excision of approximately 1 cc of cerebral cortex tissue, and it is possible that needle core brain biopsies would have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Biofluids and PET imaging approaches have so far been unsuccessful in providing the required accuracy for identifying LBD [113][114][115]. Simulation studies have suggested that cortical biopsy [116][117][118][119] would have high sensitivity and specificity for DLB, and usage of needle cores rather than open biopsy may reduce morbidity to acceptable levels [116]. Biopsy of the peripheral nervous system [120], particularly the submandibular gland [121][122][123][124], also shows promise for diagnosing DLB.…”
Section: Plos Onementioning
confidence: 99%
“…Biofluids and PET imaging approaches have so far been unsuccessful in providing the required accuracy for identifying LBD [113][114][115]. Simulation studies have suggested that cortical biopsy [116][117][118][119] would have high sensitivity and specificity for DLB, and usage of needle cores rather than open biopsy may reduce morbidity to acceptable levels [116]. Biopsy of the peripheral nervous system [120], particularly the submandibular gland [121][122][123][124], also shows promise for diagnosing DLB.…”
Section: Plos Onementioning
confidence: 99%
“…Biofluids and PET imaging approaches have so far been unsuccessful in providing the required accuracy for identifying LBD [112][113][114]. Simulation studies have suggested that cortical biopsy [115][116][117][118] would have high sensitivity and specificity for DLB, and usage of needle cores rather than open biopsy may reduce morbidity to acceptable levels [115]. Biopsy of the peripheral nervous system [119], particularly the submandibular gland [120][121][122], also shows promise for diagnosing DLB.…”
Section: Discussionmentioning
confidence: 99%
“…Biofluids and PET imaging approaches have so far been unsuccessful in providing the required accuracy for identifying LBD [87][88][89]. Simulation studies have suggested that cortical biopsy [90][91][92][93] would have high sensitivity and specificity for DLB, and usage of needle cores rather than open biopsy may reduce morbidity to acceptable levels [90] but would not detect AD-LB subjects as they mostly lack cortical LB pathology. Biopsy of the peripheral nervous system [94], particularly the submandibular gland [86;95-97], shows Faster Decline with Unsuspected Lewy Bodies promise for diagnosing DLB but peripheral LBD pathology is relatively rare in AD-LB.…”
Section: Discussionmentioning
confidence: 99%